2002
DOI: 10.1200/jco.2002.20.6.1456
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Breast Cancer: Significantly Enhanced Response With Docetaxel

Abstract: NA DOC resulted in substantial improvement in responses to DOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
166
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(175 citation statements)
references
References 38 publications
6
166
0
3
Order By: Relevance
“…In addition to pathologic complete response, we also analyzed tumor volume reduction in all tumors, where we utilized a very standard and practical approach in estimating tumor volume reduction. We believe the method reported in this study is at least as objective, if not more, compared with other methods, [26][27][28] and yet quite simple compared with MD Anderson method 29 of estimating tumor volume reduction. This method made it possible to compare the differences between different tumor categories with confidence.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to pathologic complete response, we also analyzed tumor volume reduction in all tumors, where we utilized a very standard and practical approach in estimating tumor volume reduction. We believe the method reported in this study is at least as objective, if not more, compared with other methods, [26][27][28] and yet quite simple compared with MD Anderson method 29 of estimating tumor volume reduction. This method made it possible to compare the differences between different tumor categories with confidence.…”
Section: Discussionmentioning
confidence: 70%
“…Preliminary results showed an overall response rate of 100% (complete response, 11%; partial response, 89%) with one patient (11%) showing a partial pathological response and one patient (11%) showing a minor pathological response. The Aberdeen Breast Study group is conducting a phase III trial in patients with stage III or LABC using docetaxel in sequential fashion following an anthracyclinebased cyclophosphamide/doxorubicin/vincristin/prednisolone (CVAP) regimen (Smith et al, 2002). In patients with tumours unresponsive to CVAP, docetaxel induced a 55% clinical response and a 2% pCR rates.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the breast preservation rate may be based on an improvement in the clinical response rate. Two randomized Phase III studies 20,21 have demonstrated improvements in clinicopathologic response rates with the sequential addition of docetaxel to an anthracycline-containing preoperative regimen, i.e., the Aberdeen Breast Centre trial and the NSABP B-27 trial. In the Aberdeen trial, patients receiving docetaxel had an increased breast conservation rate (67% vs. 48%).…”
Section: Discussionmentioning
confidence: 99%